ANALYSIS OF THE INFLUENCE OF LABOR, INVESTMENT, AND INFLATION ON THE GROWTH OF THE MANUFACTURING INDUSTRY IN EAST JAVA FROM 2008-2023 - Aldian Jodi Pemana Wijaya; Budi Prayitno; Eva Wany (International Journal of Accounting Innovation, 2026)
Objective : This study analyzes the impact of labor, investment, and inflation on the growth of the manufacturing sector in East Java Province during 2008–2023. Method: Using an explanatory quantitative approach with a log-linear multiple regression model and annual secondary data from the Central Statistics Agency (BPS). Results: The results show that labor has a positive and significant effect, while inflation has a negative and significant effect on industrial growth. Investment has a positive but statistically insignificant impact. Simultaneously, all three variables show significant influence with an Adjusted R² of 80.76%. These findings highlight the importance of industrial development policies that consider workforce quality, inflation stability, and investment effectiveness. Novelty: This study provides empirical evidence on the simultaneous impact of labor, investment, and inflation on manufacturing sector growth in East Java Province during 2008–2023 using a log-linear multiple regression model with long-term annual data.